Computation of thermophysical properties for magnetite-based hyperthermia treatment simulations using infrared thermography. (June 2020) - Garrido, I.; Lagüela, S.; Román, J.V.; Martín-del Valle, E.M.; González-Aguilera, D.
Highlights: Heat convection coefficient calculation for hyperthermia treatment simulations. In vitro tests with divers magnetite nanoparticle concentrations and petri dishes. InfraRed thermography for the acquisition and monitoring of temperature values. Development of a model of heat transfer based on newton's cooling law. Results obtained constitute a starting point in simulation tools. Abstract: In the biomedicine field, the application of temperature variations, both spatially and temporally, on the surface and subsurface of the human body is becoming increasingly important. Proof of this is the increasing appearance of different types of hyperthermia treatments for the apoptosis of malignant cells, minimising the damage to the healthy cells. The hyperthermia treatment with magnetite (Fe3 O4 ) nanoparticles is one of the newest, in which the knowledge of accurate values of the thermophysical properties of the elements involved in the treatment is recommended for its study in simulation tools, allowing the latter to predict the response of the organ to be treated before its application and without the need to perform in vivo tests for the particular purpose of characterisation. The InfraRed Thermography technique is used in this paper for the acquisition and monitoring of temperature values in the regions of interest, with the support of a series of thermal image processing algorithms, in order to use them in a heat transfer model developed, allowing the computation of the thermophysical properties useful for the simulation of hyperthermia treatment with magnetite nanoparticles directly from in vitro tests and with no disruption, towards an optimal design of the treatment. To achieve this objective, the validity of InfraRed Thermography for measuring temperature on in vitro tests and a temperature measurement protocol has been previously tested and designed, respectively, through the analysis of six different in vitro tests. Consistent results are obtained, ending with critical conclusions for future approaches.